Effect of vitamin D3 supplementation on serum 25 (OH)D Levels, hand grip strength, blood sugar levels, and cognitive function in the elderly - Probosari, Enny; Subagio, Hertanto Wahyu; Winarni, Tri Indah; Nugroho, Heri; Manikam, Nurul Ratna Mutu (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
ABSTRACTBackground: The aging process in the elderly can be caused by a decrease in vitamin D precursors and reduced Vitamin D levels due to impaired absorption of Vitamin D. Vitamin D plays a role in cognitive function, acts as an immunomodulator affecting blood glucose levels, promotes muscle atrophy, and affects the intranuclear VDR concentration and gene expression of VDR.Objectives: To determine the effect of vitamin D3 supplementation on Serum 25(OH)D levels, hand grip strength, blood sugar levels, and cognitive function in the elderly.Materials and Methods: This study used a quasi-experimental pre-posttest control group design with a total of 60 subjects included and divided into two groups. The treatment group received vitamin D3 at a dosage of 1000 IU/day for three months, while the control group was given a placebo. Blood serum levels were used to obtained serum 25(OH)D and blood sugar level. Hand grip strength values were measured by a hand grip dynamometer, and cognitive function was assessed using the Mini-Mental State Examination (MMSE) Questionnaire. The data was analyzed using the Wilcoxon test, and the bivariate analysis was performed using the Mann-Whitney test.Results: Most subjects were between 60 and 92 years old and had a vitamin D deficiency. Significant (P<0,05) differences were observed in serum 25(OH)D levels, blood sugar levels, and cognitive function following the intervention. The differences in serum 25(OH)D levels were 8,50±6,17, blood sugar levels were -21,68±25,88, and cognitive function was 2,23±3,05. Additionally, hand grip strength increased after the intervention (mean=0,42±4,66) but was not statistically significant (P=0,633).Conclusion: There is an improvement in cognitive function and a decrease in blood glucose levels, along with an increase in 25(OH)D levels after three months of vitamin D supplementation. However, hand grip strength did not significantly increase after supplementation.Keywords: Vitamin D3 Supplementation; serum 25(OH)D; hand grip strength; blood sugar level; cognitive function; elderly.